Reflectance Confocal Microscopy as an Aid to Dermoscopy to Improve Diagnosis on Equivocal Lesions: Evaluation of Three Bluish Nodules - Sara Bassoli; Stefania Seidenari; Giovanni Pellacani; Caterina Longo; Anna Maria Cesinaro (Dermatology Research and Practice)
Nodular lesions can be difficult to diagnose under dermoscopy alone, since they often lack specific diagnostic features. Confocal microscopy can be used as an aid to dermoscopy, to increase the diagnostic accuracy on equivocal skin lesions. We report three cases of bluish nodular lesions, difficult to diagnose under dermoscopy alone. Confocal features were very useful in these cases to lead us to the correct diagnosis, recognizing benign versus malignant entities. Histopathology is also reported, with high correspondence compared to the confocal imaging.